Elastohydrodynamic Simulation of Pneumatic Sealing Friction Considering 3D Surface Topography. Issue 1 (30th November 2022) - Bauer, Niklas; Baumann, Matthias; Feldmeth, Simon; Bauer, Frank; Schmitz, Katharina
Abstract: This contribution presents an elastohydrodynamic lubrication (EHL) model for pneumatic spool valves. For an accurate estimation of the transient friction of this tribological sealing system, the surface topography of the cylindrical sealing counterfaces of the valve housings are measured and analyzed with an optical surface measurement instrument. Based on the surface topography data, tribological properties and flow factors of the system are derived. It has been found that the consideration of the surface topography has a significant influence on the simulation results of the EHL model, lowering the calculated friction force by up to 20 %. Abstract : The influence of the surface topography of the sealing counterface in a pneumatic spool valve on the sealing friction force during operation is investigated. For that, the 3D surface topography of the running surface has been measured optically. Using an elastohydrodynamic lubrication simulation, it could be demonstrated that the surface topography reduces the friction force by about 20 %.